2018
DOI: 10.1007/s00604-018-2749-y
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric determination of the Escherichia coli DNA using a screen-printed carbon electrode modified with polyaniline and gold nanoparticles

Abstract: The authors describe an electrochemical assay for fast detection of Escherichia coli (E. coli). It is based on a dual signal amplification strategy and the use of a screen-printed carbon electrode (SPCE) whose surface was modified with a polyaniline (PANI) film and gold nanoparticles (AuNPs) via cyclic voltammetry (CV). In the next step, avidin was covalently immobilized on the PANI/AuNP composite on the SPCE surface. Subsequently, the biotinylated DNA capture probe was immobilized onto the PANI/AuNP/avidin-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Electrochemical DNA biosensors represent an exciting approach to the fast, low-cost detection of clinically important biomarkers [9,10] at the point of care [11]. A range of electrode materials and electrochemical measurement approaches have been employed for sensitive measurements (cyclic voltammetry [12], differential pulse voltammetry [13], square wave voltammetry [14] and electrochemical impedance spectroscopy [15]). The potential of electrochemical biosensors, once matured as a technology to provide efficient clinical workflows is immense.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical DNA biosensors represent an exciting approach to the fast, low-cost detection of clinically important biomarkers [9,10] at the point of care [11]. A range of electrode materials and electrochemical measurement approaches have been employed for sensitive measurements (cyclic voltammetry [12], differential pulse voltammetry [13], square wave voltammetry [14] and electrochemical impedance spectroscopy [15]). The potential of electrochemical biosensors, once matured as a technology to provide efficient clinical workflows is immense.…”
Section: Introductionmentioning
confidence: 99%
“…Omidfar et al fabricated an ultrasensitive sensing platform for detecting E. coli utilizing surface modified screen‐printed carbon electrode by first polyaniline film and then AuNP. In the next step, avidin, followed by biotinylated DNA probe was immobilized covalently on the modified electrode by avidin–biotin interaction . The described electrochemical assay was found to detect 4*10 6 to 4 CFU of E. coli and concluded that this geneosensor had potential for accurate and rapid diagnosis of E. coli imposed infections.…”
Section: Intrinsically Conductive Polymer Composites For Biosensing Amentioning
confidence: 96%
“…Various graphene-based nanocomposites were also reported for the detection of Salmonella enterica and Escherichia coli [271,278,279]. Moreover, gold nanoparticles have also been extensively incorporated into electrochemical biosensors used in food born pathogen detection, due to their excellent physiochemical properties and biocompatibility [280][281][282][283].…”
Section: Electrochemical Biosensors For the Detection Of Foodborne Pamentioning
confidence: 99%
“…In voltammetric techniques such as cyclic voltammetry, differential pulse voltammetry, or square wave voltammetry, the current caused by an electrochemically active redox probe which is directly or indirectly related to the analyte concentration, is measured by varying the potential of the working/sensing electrode. Such voltammetric biosensor platforms have been successfully utilized to detect food-borne pathogens in recent years [282,284]. In amperometric biosensors, the potential of the sensing electrode is maintained at a constant value with respect to a reference electrode and the current is measured as a function time [285].…”
Section: Electrochemical Biosensors For the Detection Of Foodborne Pamentioning
confidence: 99%